89 Conducting remote asthma reviews to increase accessibility: best practice. (16th November 2020) - Chaudhri, Nabila; Cooper, Alison; Haque, Farah
Abstract : At Babylon GP at Hand we have been providing asthma reviews via telephone and video initially. A search enables us to highlight patients due a review; those patients are invited to book a digital appointment. Follow-up messages & other methods are used to engage 'non-responders'. Increased accessibility: Appointments are made by patients through an app and conducted remotely & available also during evenings & weekends to increase accessibility. Use of Clinical Pharmacists Asthma reviews are mainly conducted by clinical pharmacists (& independent prescribers). They are trained to monitor, optimise & prescribe treatment. Reviews include monitoring symptoms, inhaler technique, triggers, smoking status, hospital admissions and provision of personalised asthma action plans. Pharmacists can refer patients to GP's, where they are complex. Empowering patients: Consultation notes are documented in a 'patient friendly' manner and shared with patients via the app. Safety netting, including, information such as 'what to do during an asthma attack' is easily accessible. Asthma actions plans are also emailed to patients. More accessible information empowers the patient to take greater ownership of their health and condition. Physical follow-up: Pharmacists and other healthcare professionals can refer patients for a physical follow up if necessary. This can include a chest examination in an acute exacerbation or a referral for an objective test such as spirometry. Patients can be referred to one of five locations at a convenient date, time and location via an automated link in the app. Pharmacists can prescribe or ask the patient to purchase a peak flow meter to minimize risk. They are also able to provide written instructions in the app on how to measure and record measurements. We will be reviewing outcomes of all patients suffering from asthma closely over the next 12 months and obtaining feedback from patients and clinicians involved in their care.